Modern family. The complete seventh season [videorecording (DVD)] - O'Neill, Ed, 1946-; Burrell, Ty, 1967-; Vergara, Sofía, 1972-; Bowen, Julie; Ferguson, Jesse Tyler; Stonestreet, Eric, 1971- (20th Century Fox Home Entertainment, 2015)
Enjoy a new chapter of love and laughter with the Seventh Season of the show. Quackery rules the roost when Phil adopts a trio of orphan ducklings and the rebellious Dunphy kids spread their wings. Meanwhile, Cam and Mitchell face financial hurdles and wild frat boys, Jay and Gloria 'farm' out Joe's preschool education and Manny leaps into the dating game. But will the big question finally be answered: are Haley and Andy destined to be together?